THE EFFECT OF ENTREPRENEURSHIP EDUCATION AND EMOTIONAL INTELLIGENCE OF INTEREST THROUGH ATTITUDE ENTREPRENEURSHIP GENERATION Y - Prevista Fakhrun Nisa; Syamsul Arifin (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2020)
Entrepreneurship education not only provides a theoretical foundation of the concept of entrepreneurship but to shape attitudes, behaviors, and thought patterns (mindset) of an entrepreneur (entrepreneur). This is an investment in human capital to prepare the generation Y in starting a new business through the integration of experience, skills and knowledge necessary to develop and expand a business. Entrepreneurship education can also increase the interest of generation Y to choose entrepreneurship as a career option in addition to career options become private sector employees, civil servants or employees of state-owned enterprises which can significantly drive attitudes, behaviors, and interests toward entrepreneurship.